Jampi: Satu Kajian Hukum Menurut Al-Sunnah - Abd. Rahman, Mohd. Muhiden (Jurnal Usuluddin, 1995)
The Charm (al-Ruqa) is one of the Islamic medicine and it was based on two principles, i.e. prevention and cure. The approach of this charm is practice and hadith. Therefore this article discusses the concept of the Charm (al-Ruqa) in Islam without ignoring it’s "hukum" in hadith view.